Geographical Distribution of Power Plants in Iraq in 2015 Using Geographic Information Systems (Journal of the College of Education for Women, 2020)
The study aims to study the geographical distribution of electricpower plants in Iraq, except the governorates of Kurdistan Region (Dohuk, Erbil, Sulaymaniyah) due to lack of data.In order to reach the goal of the research was based on some mathematical equations and statistical methods to determine how the geographical distribution of these stations (gas, hydropower, steam, diesel) within the provinces and the concentration of them as well as the possibility of the classification of power plants in Iraq to facilitate understanding of distribution in a scientific manner is characterized by objectively.The most important results of the research are that there are a number of factors that led to the irregular distribution of these stations in the provinces, which led to a discrepancy due to the existence of variation in the same provinces because of the components (population, security situation, economic, geographical location) There are deterministic determinants forcing the decision maker to create certain type of stations without others in this province without others.